The new invisible college science for development - Wagner, Caroline S.; ProQuest (Firm) (Washington, D.C. : Brookings Institution Press, 2008)
"Combines quantitative data and extensive interviews to map emerging global science networks and trace the dynamics driving their growth. Argues that the shift from big science to global networks creates unprecedented opportunities for developing countries to tap science's potential. Offers a guidebook and playbook for policymakers confronting science's transformation"--Provided by publisher.
The new invisible college emerges -- The topology of science in the twenty-first century -- Networked science -- Tectonic shifts : the rise of global networks -- The virtual geography of knowledge -- Scientific capacity and infrastructure -- Governing the new invisible college.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Science and state; Science -- Study and teaching -- International cooperation; Global method of teaching; Research -- International cooperation; Information networks; Electronic books